2019
DOI: 10.1111/ajd.13169
|View full text |Cite
|
Sign up to set email alerts
|

Allergic contact dermatitis in children and proposal for an Australian Paediatric Baseline Series

Abstract: Background Allergic contact dermatitis (ACD) is an increasingly common diagnosis in children. The objectives of this study were to review our experience with ACD in children in tertiary settings, to ascertain the spectrum of allergens in this population and to subsequently propose the first Australian Paediatric Baseline Series for patch testing. Methods We conducted a retrospective analysis of patch test data from 1993 to 2017 from two tertiary referral patch‐testing centres in Melbourne, Victoria. Results A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
2
11
1
Order By: Relevance
“…A considerable percentage (10.4%) of our patients in the present study were pediatric patients who were <18 years old. Although contact sensitization to MCI/MI and MI is usually less frequent among pediatric patients, 39,40 recent reports showed high sensitization prevalences up to 11% among children who underwent patch testing 41 . Atopic dermatitis was suggested as a risk factor for MCI/MI sensitization, 36,38 however, the number of patients with atopic dermatitis or atopic skin diathesis was relatively low in our study.…”
Section: Discussioncontrasting
confidence: 60%
“…A considerable percentage (10.4%) of our patients in the present study were pediatric patients who were <18 years old. Although contact sensitization to MCI/MI and MI is usually less frequent among pediatric patients, 39,40 recent reports showed high sensitization prevalences up to 11% among children who underwent patch testing 41 . Atopic dermatitis was suggested as a risk factor for MCI/MI sensitization, 36,38 however, the number of patients with atopic dermatitis or atopic skin diathesis was relatively low in our study.…”
Section: Discussioncontrasting
confidence: 60%
“…In recent years, unique patch test series have been developed to facilitate diagnosis and management of ACD in children 8,10 . Our rates of sensitization and relevant positive patch tests are similar to other studies published in the past decade 8,11,12 …”
Section: Discussionsupporting
confidence: 73%
“…Pediatric ACD is increasing in prevalence. A meta‐analysis done found that studies published after 1995 have reported higher rates of positive patch tests 8,9 . In recent years, unique patch test series have been developed to facilitate diagnosis and management of ACD in children 8,10 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been also previously reported for fragrance mix [ 41 43 ], balsam of Peru [ 44 47 ], thiomersal [ 48 ], and cobalt chloride [ 44 , 49 , 50 ]. The relation of atopies and atopic dermatitis/atopies to allergen sensitization has been discussed in the literature mostly for pediatric populations [ 51 , 52 ], yet very few reports [ 53 , 54 ] are available for adult populations, which is a question our present work addresses. Although there is a close relation between the presence of atopy and contact dermatitis, not much is known about the effect of atopy in the allergen contact sensitization.…”
Section: Discussionmentioning
confidence: 99%